“Juegos colaborativos para desarrollar la psicomotricidad y autonomía en niños de 3 a 4 años” - Caizaluisa Ramirez, Karem Lisbeth (2024)
Education at an starting level allows the competencies ‘development, skills and abilities in children from 3 to 4 years old, the autonomy development and psychomotor skills being so transcendental to improve the learning and coexistence. The purpose of the present research project was to make evident the shortcomings that children show in psychomotor skills, taking in mind that this is a key area in child development, Its just there where the need arises to investigate autonomy and psychomotor skills based on implementation of collaborative work in children aged from 3 to 4 years. Therefore, to respond to the shortcomings, the following